DEVELOPMENT OF PROCEDURES FOR MODIFYING THE CIPHER GOST 28147 - Сергій Євсєєв; Роман Корольов; Андрій Ткачов; Анастасія Німченко (Сучасні інформаційні системи, 2021)
The entry of mankind into the era of high technologies, the rapid growth of computer technology contributes to the expansion of the range of electronic services. To ensure the security of confidential information, personal data, cryptographic systems of traditional cryptography (symmetric cryptosystems) and public key cryptography (asymmetric cryptosystems) are used. As a rule, the former provides security services, the latter provide key distribution. However, in the conditions of totalitarian surveillance in society by the special services of developed countries, cryptographic tabs are embedded in cryptographic algorithms, which, on the one hand, provide “quick” access for special services to confidential information, and on the other hand, allow intruders to break into the cryptosystem and obtain user data. The article proposes a modification of the well-known GOST 28147-89 algorithm, which ensures the "elimination" of possible crypto-bookmarks and an increase in crypto-resistance in the post-quantum period (the emergence of a full-scale quantum computer that allows hacking modern symmetric and asymmetric cryptosystems based on Grover and Shor algorithms). It is proposed to use the procedures for modifying the block-symmetric encryption algorithm (BSEA) GOST 28147-89 (2009, 2015) in OFB mode, which will make it possible to form a pseudo-random sequence based on dynamic changes in the S-box, and provide the required level of security.